The Dialectology of Late Jewish Literary Aramaic - Kaufman, Stephen A. 194X- (Aramaic studies, 2013)
‭This study attempts to disambiguate the various subdialect groups within the corpus of late Targum and Targum-like texts grouped together under the rubric of Late Jewish Literary Aramaic (LJLA) in the database of the online Comprehensive Aramaic Lexicon Project. The relationship with the Syriac lexicon was tested separately for each text in the group. The result shows five distinct groups within the larger corpus ranging from texts ‘translated’ from Syriac to texts showing little contact at all with native Aramaic traditions. A particularly surprising result was that Targum Sheni appears to belong to the core group of LJLA texts.‬